Model of Building Institutional Networks in Early Prevention of Social Conflicts in Urban Area of Bekasi - Andi Sopandi; Yogi Suprayogi Sugandhi; Wahyu Gunawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study discusses Building an Institutional Network for Early Prevention of Social Conflict in urban areas, a case study in Bekasi City, West Java Province, Indonesia. The purpose of this study is to find out: (1) to study the institutional network pattern of early prevention of social conflicts (conflicts over erection of places of worship, conflicts of a Primodial nature, and conflict of economic interests) in urban areas, especially Bekasi City, based on three institutional pillars, namely the Regulative pillar, Normative pillars, and Cognitive-cultural Pillars as stated by Scott (2001); (2) analyze other aspects that affect the institutional network in the early prevention system of social conflict in urban areas; and (3) examines the model of institutional networks in early social conflict prevention systems in urban areas. The research method used to explore and identify building institutional networks in early prevention in urban areas is qualitative. The model of building an institutional network in the early prevention of social conflict in urban areas, is very dependent on the set structure, which was developed, including.